Modeling of piecewise linear processes - Олешко, Т. І. (Proceedings of National Aviation University (archive), 2002)
The piecewise-linear process Z (t) - {Zx (t), Z 2 (t), ..., Z n (ε)), which determines the behavior, is considered.an enlarged unit